Dilemmas of Financial Reporting as the Reliable Information Source of an Entity Performance Results - Zuchewicz, Joanna (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2012)
The objective of the hereby paper is to indicate, on the one hand, the need for transformations in financial reporting as the basic source of information about the financial situation of an economic entity indispensable in the decision making process by its users, and on the other to provide the analysis of the adopted reporting reconstruction directions validity, as suggested by international financial community. On the basis of comments and reservations presented by practitioners and the analysis of research conducted by scientific circles the thesis is put forward by the Author that the suggested extension of information scope to be disclosed in obligatory financial reports proposed by the authorities responsible for the preparation of international accounting standards will not increase the usefulness of information they include and will not influence higher security of business transactions. The paper is divided into there interrelated parts. The first presents the overview of critical opinions expressed by financial circles regarding accounting as the system generating information about the achievements of entities operating at the global market. The second refers to an entity stakeholders and their information needs. Irrespectively of opinions about the primacy of investors and their rights in making investment decisions it is of great importance to meet the needs of the remaining interest groups by means of providing both reliable and useful information in financial statements. The final part of the paper presents an outline of undertaken and suggested restructuring directions in financial reporting proposed by IASB and FASB, as the institutions responsible for preparing international accounting standards. This part also discusses the selected suggestions by Polish researchers regarding the form and content of particular components included in a financial statement.